Pengaruh Academic Burnout Terhadap Mekanisme Coping pada Mahasiswa Akhir di Yogyakarta - Anissa Prisilla Bahari; Agus Salim (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Academic burnout is the condition of a person who feels tired of the academic process and shows low achievement. Coping mechanisms are all efforts to resolve problems that are used as a defense to protect oneself. The aim of this research is to analyze the influence of academic burnout on coping mechanisms among final students in Yogyakarta. The research subjects were final students aged 20-25 years in Yogyakarta with a total of 135 students, who were obtained using purposive sampling techniques. This research uses quantitative research methods with data management techniques using regression analysis. From the results of the product moment analysis, the correlation coefficient r = -0.601 with p = 0.000 is obtained, so there is a negative influence between the academic burnout variable and the coping mechanism variable in final students. This shows that the hypothesis in this research is accepted. This negative influence means that the higher the level of academic burnout experienced by students, the lower the ability of their coping mechanisms.